Pelatihan penyusunan proposal PTK bagi Guru Sekolah Dasar di Kabupaten Pinrang - Muhammad Danial; Wahidah Sanusi (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The objectives to be achieved through IbM activitiesare teacher: understanding of the principles and technical ofClassroom Action Research (CAR), steps of CAR activity,understand the format and components of the CAR proposaland skillfully preparing to conduct and to write CAR proposaland to produce CAR proposal draft. The method used toachieve these objectives are : to present about principles and toconduct CAR, and to write main essential CAR proposal draftby Servant team, practice of CAR conducting and writingCAR proposal draft of worksheet by participants, and topresent of CAR product by participants, and observe andinterviews to participants conducted after and while thisactivity. The activity participants are teachers of StateSecondary School of number 4 Pinrang regency City whichamounts 14 persons. The results obtained after the IbMactivities carried out are (1) The participants (teachers fromSDN of number 4 Pinrang regency) has been understood aboutthe principles and technical of Classroom Action Research(CAR), steps of CAR activity, understand the format andcomponents of the CAR proposal draft and skillfully preparingto conduct and to write CAR proposal, and to produce CARproposal draft and (2) The participants is very enthusiast for tojoin the CAR workshop activity and to give positive responseof the IbM activity.